Prevalence, Risk Factors, and Management of Hansen’s Disease in Indonesia: Evidence from A Systematic Literature Review - Meidyta Sinantryana Widyaswari; Lysa Veterini; Hotimah Masdan Salim (Jurnal Ilmu Kesehatan dan Kesehatan, 2025)
Background: Hansen’s disease (leprosy) continues to be a public health concern in Indonesia, which ranks among the countries with the highest case numbers globally. Despite national control programs, the detection of new cases and disability rates suggests ongoing transmission and delays in diagnosis. A clearer understanding of prevalence, risk determinants, and management approaches is critical to strengthen interventions. Methods: A systematic literature review was performed using PRISMA guidelines. Relevant studies published between 2014 and 2024 were identified from PubMed, Scopus, and Google Scholar. Eligible publications included original research or program evaluations conducted in Indonesia. From 423 records initially screened, 76 full texts were assessed, and 22 articles met the inclusion criteria. Extracted data included prevalence, associated risk factors, and management strategies. Results: The reviewed studies originated from multiple regions such as Java, Sulawesi, Papua, and Maluku. Study designs comprised cross-sectional surveys, case–control studies, cohort analyses, and program evaluations. Prevalence varied substantially, with Papua, Sulawesi, and Maluku reporting the highest burdens. Commonly reported risk factors were poverty, overcrowded housing, malnutrition, genetic predisposition, and persistent social stigma. Household exposure and treatment delay were additional contributors to transmission. Management strategies mainly emphasized multidrug therapy (MDT) adherence, disability prevention, and stigma reduction. Community education and early case detection programs were associated with improved outcomes. However, several barriers remain, including incomplete adherence, inadequate health worker training, and limited psychosocial support. Conclusion: Hansen’s disease in Indonesia remains endemic in several provinces and is shaped by interconnected socioeconomic and biological factors. While MDT has reduced transmission, substantial gaps exist in disability prevention and stigma management. Enhanced surveillance, improved early detection, and stronger integration of community-based and psychosocial strategies are urgently needed to support national and global elimination goals.